Associations between Toxoplasma gondii infection and steroid hormone levels in spotted hyenas. (April 2022) - Laubach, Zachary M.; Gering, Eben; Yang, Erik; Montgomery, Tracy M.; Getty, Thomas; Holekamp, Kay E.
Abstract: Toxoplasma gondii is a common parasite that infects warm-blooded animals and influences host physiology. T. gondii is known to target the host's central nervous system, affecting circulating levels of steroid hormones, fear-related behaviors, and health, although these effects appear to vary among host taxa. Here, we investigated the relationship between T. gondii infection and levels of plasma testosterone and cortisol within a wild population of spotted hyenas ( Crocuta crocuta, n = 109). In our analyses, we accounted for age and sex via stratified regression analyses. We detected a negative association between circulating plasma testosterone and T. gondii infection among female cubs and subadults as well as adult male hyenas. We found no associations between T. gondii infection and cortisol in any age class or sex group of hyenas. Our work adds to a growing body of literature by characterizing the relationship between T. gondii infection and physiology in a novel host in its natural habitat. In a broader context, our findings indicate that responses to infection vary with characteristics of the host and point to a clear need for additional studies and priorities for future work that include diverse taxa and ecological settings. Graphical abstract: Image 1 Highlights: Toxoplasma gondii infects diverse hosts and leads to differences in hormone levels. The relationship between T. gondii infection and host hormone response is mixed. We assessed if wild spotted hyena hormones differed by T. gondii infection. Testosterone was lower in infected female cub/subadult and adult males hyenas. Our results parallel laboratory findings but provide added realism of a wild animal.